A study of the market reaction towards board of director changes announcement in Malaysia / Nur Azura Hassan - Hassan, Nur Azura (2007)
This study investigates the market reaction towards the board of director changes announcement in Malaysia. The study period covers from January 2006 to December 2006. This study used standard event study methodology to find the stock reactions towards those announcements. From the 60 companies selected, this study of new appointments and resignations announcement reveals that there was no significant effect on the wealth of the concern firms. From the test period of 30 days before and after the announcements, this study found that there were no significant relationship between average abnormal returns and cumulative abnormal returns around the announcement day. The CAR on day -30, -3 is 1.62%, while the CAR for five day event window (-2, +2) is 0.22%. The last one is the third event window (+3, +30), where it consists of 28 days. The CAR for the third event window is 1.700.10. As a conclusion, this hypotheses testing determined that in answering the Hypothesis 1 and Hypothesis 2, the researcher rejects Ha and does not reject Ho. That means, there were no significant relationship between average abnormal returns and cumulative abnormal returns around the announcement day.